Alpha-1-Microglobulin: epidemiological indicator for tubular dysfunction induced by cadmium?. Issue 7 (July 1998) - Pless-Mulloli, T; Boettcher, M; Steiner, M; Berger, J
Abstract : OBJECTIVES: To evaluate the suitability of alpha-1-microglobulin as a marker for cadmium induced renal dysfunction. METHODS: alpha-1-Microglobulin was studied in a cross sectional survey in relation to the body burden of cadmium. Concentrations of alpha-1-microglobulin in 24 h urine of 831 people aged 2-87 years were analysed in association with urinary cadmium excretion, cadmium blood concentration, age, sex, occupational and smoking history, and estimated creatinine clearance. Participants came from a population residentially exposed to cadmium and from two control populations matched for socioeconomic status. RESULTS: The excretion of alpha-1-microglobulin/24 h ranged from 0.1 mg to 176.3 mg and 44.4% of samples showed concentrations near the detection limit. Ordinal logistic regression analysis of people of all ages identified a high risk only for males compared with females (odds ratio (OR) 2.14; 95% confidence interval (95% CI) 1.56 to 2.94), age group, and duration of living on contaminated soil (OR 1.03/year; 95% CI 1.02 to 1.04), but not urinary cadmium excretion (OR 1.30; 95% CI 0.96 to 1.77) as significant predictors. For people < or = 50 years of age a weaker effect of sex (OR 1.76; 95% CI 1.13 to 2.73) and age group and an effect of similar magnitude for the duration of soil exposure (OR 1.03; 95% CI 1.01 to 1.04) were found. Also, the urinary cadmium excretion (OR 2.26; 95% CI 1.38 to 3.70) and occupational exposure (OR 1.71; 95% CI 1.03 to 2.83) were found to be significant in this younger age group. The estimated creatinine clearance had no significant impact on the alpha-1-microglobulin excretion. CONCLUSION: alpha-1-Microglobulin is a suitable marker for early tubular changes only for people < or = 50 years. It may not be sufficiently specific for cadmium, and therefore not a suitable surrogate for cadmium exposure in epidemiological studies.